Is Increasing Inorganic Fertilizer Use in Sub-Saharan Africa a Profitable Proposition? Evidence from Nigeria - Liverpool-Tasie, Lenis Saweda O.; Omonona, Bolarin T.; Sanou, Awa; Ogunleye, Wale (World Bank Group, Washington, DC, 2015)
Inorganic fertilizer use across Sub-Saharan Africa is generally considered to be low. Yet, this belief is predicated on the assumption that it is profitable to use rates higher than currently observed. However, there is little rigorous empirical evidence to support this notion. Using a nationally representative panel data set, and with due recognition of the role of risk and uncertainty, this paper empirically estimates the profitability of fertilizer use for maize production in Nigeria. The analysis finds that inorganic fertilizer use in Nigeria is not as low as conventional wisdom suggests. Low marginal physical product and high transportation costs significantly reduce the profitability of fertilizer use. The paper finds evidence that strategies to reduce transportation costs are likely to have a much larger effect on the profitability of fertilizer use than fertilizer subsidies. Apart from reduced transportation costs, other constraints such as timely access to the product; availability of complementary inputs such as improved seeds, irrigation, and credit; as well as good management practices are also necessary for sustained agricultural productivity improvements.